(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article highlights the fact that today social advertising serves as an active tool that fully affects a wide audience in eliminating important social problems in society. In particular, in order to highlight the lexical-syntactic and pragmatic features of social advertisements in Uzbek and English, a comparative analysis was carried out, dividing them into several areas.